Scheduling optimum planting window for gladiola based on El Niño Southern Oscillation (Scientia Agricola, 2020)
Gladiola is an important cut flower worldwide and scheduling field gladiola production is largely dependent on planting at the correct time since its development is controlled by the air temperature. The aim of this study was to configure a planting window of gladiola in order to harvest spikes to be sold on All Souls’ Day and Mother’s Day holidays in the state of Rio Grande do Sul, Brazil, taking into account the El Niño Southern Oscillation (ENSO) phases. The PhenoGlad model, a dynamic process-based simulation model that simulates gladiola phenology on a daily time step was used in this study. Daily minimum and maximum temperatures over 55 years (1961-2015) from 18 weather stations across Rio Grande do Sul state, Brazil, were used as input data in the PhenoGlad model. The optimum planting window was simulated for each maturity group, location and ENSO phase. For harvesting on All Souls’ Day, the optimum planting window had greater variation among the different ENSO phases. For Mother’s Day, only Very Strong El Niño events affected the development of gladiola, indicating the weak signal of the phenomenon at this time of the year. A case study in a commercial farm demonstrated the importance of these results for farmers. The planting window for production on Mother’s Day in a Neutral year was successfully configured. Determining the optimum planting window by considering the ENSO effect led to a more precise scheduling of gladiola production in southern Brazil.